2019
DOI: 10.1039/c8ob03106a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine- and water-promoted pentannulative aldol reaction

Abstract: An intramolecular aldol reaction promoted by tributylphosphine and water is described. Thereby, metal-free access to highly functionalised cyclopenta-fused arenes and heteroarenes is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The role of the solvent was subsequently investigated (entries 6–11). The polar aprotic solvents such as DMSO and acetonitrile delivered 2a in good yields (entries 8 and 9). This observation is in line with the success of the MBH or MBH-type reactions in polar media. , …”
supporting
confidence: 86%
See 1 more Smart Citation
“…The role of the solvent was subsequently investigated (entries 6–11). The polar aprotic solvents such as DMSO and acetonitrile delivered 2a in good yields (entries 8 and 9). This observation is in line with the success of the MBH or MBH-type reactions in polar media. , …”
supporting
confidence: 86%
“…With our experience in synthesizing multifunctional cyclopentanoids via organophosphine catalysis, we envisioned that the tethered α-substituted enone-aldehydes G undergo a cascade phospha-Michael/aldol reaction, akin to Morita–Baylis–Hillman (MBH) reaction, and generate the kinetically favored five-membered ring systems I (Scheme ). A subsequent 1,4-proton shift generates J , which undergoes phosphine elimination through γ-deprotonation assisted by the adventitious hydroxide, providing (hetero)­arene-fused 3-hydroxycyclopentanones K .…”
mentioning
confidence: 99%
“…This redox reaction may be facilitated by water, as it has long been known that tertiary phosphines and water form the corresponding phosphine oxides and hydrogen under alkaline conditions [41]. Furthermore, it has been shown that the attack of water on phosphonium centers leads to the elimination of the corresponding newly formed phosphine oxide [42]. In a recent publication, this reactivity is exploited in a photocatalytic phosphine-mediated water activation for hydrogenation of alkenes [43].…”
Section: Table 1 Yield and Characteristic Chemical Nmr-shifts For Zwi...mentioning
confidence: 99%
“…As part of our explorations leading to the development of the phosphine- and water-promoted reductive aldol method with α-substituted dienone-aldehydes 16 , we utilized dienone-ketones 19 , possessing enolisable protons, Scheme 10. 34 The RAR of 19 was expected to provide 20 under the prototypical conditions. But we isolated 21 , which is an intramolecular aldol product.…”
Section: Phosphine-mediated Transformations Of Activated Alkenesmentioning
confidence: 99%